Targeted Therapies in Epithelial Ovarian Cancer - Barrena Medel, Nicanor I. (Hindawi Publishing Corporation, 2010)
Epithelial ovarian cancer remains a major women's health problem due to its high lethality. Despite great efforts to develop effective prevention and early detection strategies, most patients are still diagnosed at advanced stages of disease. This pattern of late presentation has resulted in significant challenges in terms of designing effective therapies to achieve long-term cure. One potential promising strategy is the application of targeted therapeutics that exploit a myriad of critical pathways involved in tumorigenesis and metastasis. This review examines three of the most provocative targeted therapies with current or future applicability in epithelial ovarian cancer.